2010
DOI: 10.1111/j.1365-2036.2010.04283.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lesogaberan, a novel GABAB‐receptor agonist, on transient lower oesophageal sphincter relaxations in male subjects

Abstract: SUMMARY BackgroundTransient lower oesophageal sphincter relaxations (TLESRs) are a major mechanism behind gastro-oesophageal reflux disease (GERD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 33 publications
5
48
0
Order By: Relevance
“…110, 111 Therefore, more specific, peripherally acting GABA-B agonists are currently being developed that aim to overcome the central side effects. 55,112 A recent study assessed the addition of the more peripherally specific GABA-B agonist lesogaberan to conventional PPI therapy in patients with refractory symptoms and a decrease in reflux events and an increase in LOS pressure was observed. 113 However, some central side effects like headache and paraesthesia may occur when using lesogaberan.…”
Section: Gaba-b Receptor Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…110, 111 Therefore, more specific, peripherally acting GABA-B agonists are currently being developed that aim to overcome the central side effects. 55,112 A recent study assessed the addition of the more peripherally specific GABA-B agonist lesogaberan to conventional PPI therapy in patients with refractory symptoms and a decrease in reflux events and an increase in LOS pressure was observed. 113 However, some central side effects like headache and paraesthesia may occur when using lesogaberan.…”
Section: Gaba-b Receptor Modulatorsmentioning
confidence: 99%
“…113 However, some central side effects like headache and paraesthesia may occur when using lesogaberan. 112 Widespread application of GABA-B receptor modulators as add-on therapy in refractory GERD patients is likely to take place when more specific agents with fewer side effects become available.…”
Section: Gaba-b Receptor Modulatorsmentioning
confidence: 99%
“…4,5 Preclinical studies in dogs and earlyphase clinical studies in humans showed that lesogaberan decreased the number of TLESRs and episodes of gastroesophageal reflux. [6][7][8] In humans, lesogaberan also increased lower esophageal sphincter pressure. 6,7 However, as many as 50% of the healthy individuals who received lesogaberan during early Phase I clinical trials reported symptoms of paresthesia.…”
Section: Introductionmentioning
confidence: 95%
“…Second, it shows that baclofen has multiple beneficial effects on the OGJ, and that the search for well-tolerated and effective GABA-B agonists should continue. [9][10][11] Furthermore, it supports vagal stimulation by the EndoStim â device that suppresses TLOSRs, which may mimic other effects of baclofen at the OGJ without side effects. 12 Finally, the results inform the design of surgical and endoscopic anti-reflux procedures that aim to restore OGJ structure and function to normal.…”
mentioning
confidence: 99%